The role of benthic habitat mapping for science and managers: A multi-design approach in the Southeast Brazilian Shelf after a major man-induced disaster - Menandro, Pedro S.; Lavagnino, Ana Carolina; Vieira, Fernanda V.; Boni, Geandré C.; Franco, Tarcila; Bastos, Alex C. (Frontiers in Marine Science, 2022)
Seabed mapping is the baseline information for ocean managing, becoming an indispensable item for Marine Spatial Planning. Here, we use a case study and published data along the southeast Brazilian continental shelf to illustrate the concepts of benthic habitat mapping and the importance of having maps on different scales and the potential for using a multi-design approach. The case analysis uses a regional map and distinct criteria (seabed geodiversity and biodiversity, and potentially influence of the tailings plume) to define three areas along the continental shelf to be mapped in a high resolution (multibeam echosounder and subaquatic images), as part of a marine monitoring program. The background of the case study is a tailing dam failure disaster that led to the input of iron ore tailings in the ocean, leading to a major environmental disaster. Three areas were chosen, including: a Marine Protected Area, a major impacted fishing ground, and understudied reef area. Results detailed the benthoscape throughout the three areas, providing primary information for the study of benthic habitats and their distribution. The multi-design approach indicated that although a regional analysis can indicate potential vulnerability as a first assessment approach, high-resolution habitat mapping is needed to evaluate and produce a higher-confidence level for decision-makers. Having an overall view of what and where to collect would be best to inform vulnerable areas that, in this case study, could be threatened by plume dispersion and tailings accumulation. Our results subsidize the delineation of priority areas aiming for protection and guiding for other studies, besides the consolidation of habitat importance and the integration through a hierarchical classification scheme. Although Brazil has never produced a regional or national habitat map for the entire continental margin, there are already conditions to plan, execute and maintain a habitat mapping program, partnering with Universities, Government Institutions (e.g., the Brazilian Navy), and the private sector. In the context of the Ocean Decade targets, it is urgent to plan and implement a national database capable of supporting a habitat classification effort on a broader national scale, with the flexibility to support a multi-design or a multi-scale approach.